Zonificación de amenazas geológicas en el barrio Timbara del cantón Zamora, provincia de Zamora Chinchipe. - Giron Ramírez, Víctor Aurelio (2010)
This research, is threats geological in Zamora Canton Timbara district, province of Zamora Chinchipe zoning and the use of the geographic information systems (GIS). With this in mind, a set of field work was carried out and office determining susceptibility and threat assessment to determine that conditions this sector is based on a theoretical system, which is to quantitatively assess the possible constraints field factors which directly influence the emergence of new geological threats. Also determine the degree of threat and resistance of the soil on the hill where the tank sits drinking water for the neighborhood Timber. For the implementation of this project is taken as heading information digital topographic study level detail (local level); based on this information and performed field tasks sector has obtained thematic maps: geology, slopes, current use of the soil, rainfall, geotechnical among others. Each variable which is one of these thematic maps has been assessed based on the capacity each one of them to be prone to mass movements. With the help of geographic information systems, covered in digital form each of the variables analyzed for the overlay of thematic maps and get the final map showing areas of threat in the Timbara neighbor. This information in digital form as similarly serve basis and starting point for the implementation of a correct territorial legislation with a view to a sustainable development of the Timbara district, thus facilitating the decision-making and the proper management of resources.